2001
DOI: 10.1038/sj.cgt.7700292
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of dendritic cells (DCs) with the CIITA gene: increase in immunostimulatory activity of DCs

Abstract: Dendritic cells ( DCs ) are the major antigen -presenting cells. They are able to present tumor antigens to immunologic effector cells. MHC class II molecules on DC surfaces play an important role in priming effector cells against tumor cells and their antigens. The transactivator CIITA ( MHC class II transactivator ) is a non ± DNA -binding transactivator, which regulates the expression of MHC class II, HLA -DM, and invariant chain and behaves as a master controller of constitutive and inducible MHC class II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Flow cytometry showed CD14 negative populations, expressing markers typical for DC (CD80 + , CD83 + , CD86 + and HLA-DR expressing cells). The CIK cells were phenotyped with antibodies against CD3, CD8, CD16, CD40L, CD56, HLA-ABC and HLA-DR. Data was similar to other studies by our group (data not shown) [5,11,14]. …”
Section: Resultssupporting
confidence: 92%
“…Flow cytometry showed CD14 negative populations, expressing markers typical for DC (CD80 + , CD83 + , CD86 + and HLA-DR expressing cells). The CIK cells were phenotyped with antibodies against CD3, CD8, CD16, CD40L, CD56, HLA-ABC and HLA-DR. Data was similar to other studies by our group (data not shown) [5,11,14]. …”
Section: Resultssupporting
confidence: 92%
“…With the aid of liposomemediated infection, gene transfer into CD83 + DC resulted in more than 90% of the cells transduced. Using a protocol with UV-irradiated adenoviruses similar results can be obtained without addition of liposomes (Mulders et al, 1998;Märten et al, 2001). Adenoviral vectors can also be used for transduction of CD34 + cell derived DC .…”
Section: Transfection Into Dendritic Cellsmentioning
confidence: 75%
“…Studies demonstrated that IFN-γ and IL-12 play critical roles in immunotherapy using DC and CIK [28], [33]. Tumor cells are highly heterogeneous [46] and a specific tumor may contain cells with both high and low MHC-I populations [47], [48].…”
Section: Discussionmentioning
confidence: 99%